PREVALENCE OF STREPTOCOCCAL PHARYNGITIS IN PEDIATRICS. - SHABANA PRAVEEN,; PREMA. A, (International Journal of Pharma and Bio Sciences, 2014)
A microbiological diagnosis of pharyngitis is essential for confirmation of Group A Streptococci. Macrolide is given to those patients who are allergic to Penicillin. Various rates of Macrolide resistance of Streptococcus pyogenes are reported worldwide. A total of 400 children was included in the study. All samples were processed by standard Microbiological protocol. Antibiotic susceptibility testing was done for all the significant isolate. Minimum inhibitory concentration test and double disc diffusion test were done for Macrolide resistant Streptococci. All isolates were screened for the detection of biofilm formation. In this study 139(34.75%) children were positive for Beta haemolytic streptococci: Group A Streptococci 71(51.1%), Group C Streptococci 29(20.8%) and Group G Streptococci 39(28.05%). Macrolide resistance in Group A Streptococci was found to be 28.1% and Biofilm formation was 35.2%. In Conclusion this study highlights high rate of Streptococcal infection in this population and also alarmingly high rates of Macrolide resistance